Le théâtre Robin, terrain de jeu et de bataille des merveilleux scientifiques (1862-1867) - Christophe Meslin (Itinéraires)
Henri Robin, born Henri-Joseph Donckele (1811-1874), was a showman, conjurer, projectionist and popularizer of science whose career culminated in the operation of his Parisian theater from December 1862 to February 1867. During this four-year period, Henri Robin's activities – from their sources of inspiration to their media impact – reflect the major changes taking place at the time and which would contribute to redefining the words “science”, “wonder”, “supernatural”, “belief” and “progress”. Not only did Robin's shows bear witness to these changes in sensibility and representation but they also played an influential role in their dissemination. The skilful projectionist offered new insights into geology, paleontology and oceanography, and, as an experienced “showman” who had honed his skills on various European stages, he was one of the very first, if not the first, to turn electricity into a spectacle in itself, a “fairy” that fascinated, and also frightened a little. Although he shared interests and possible interactions with Hippolyte-Léon Denizard-Rivail, before the latter became the founder spiritism in 1857 under the name of Allan-Kardec, from 1863 onwards Robin also proved to be a fierce satirist of this movement, which was very much in vogue and aimed to become a scientific religion. Finally, Robin's influence seems to have extended to academic and scholarly institutions, through the example he set of spectacularizing the wonders of science and new technologies.